The trade effects of the plague: The Saminiati and Guasconi Bank of Florence (1626-1634) - Robert J. R. Elliott; Fabio Gatti; Eric Strobl (European Historical Economics Society (EHES), 2024)
This paper quantifies the impact of the 1630-1631 Italian plague on the business activities of the Florentine merchant-bank Saminiati & Guasconi. Employing AI for handwriting recognition on over 6,000 bank letters we show that letters and goods transactions decreased by two-thirds when a merchant lived in an infected town although this negative effect was halved when the correspondent also resided in an infected town. Mentions of precious coins however increased reflecting a flight to the safety of hard currency. The plague also shifted the bank's merchant network towards Southern and Eastern Europe and away from the Atlantic Coast.
Keywords: N00; N73; N83; 330; merchants; plague; trade